A Tree Inventory in The Homegarden at The Tambakrejo Village, Jombang Regency - Indah Fitriani; Anggi Indah Yuliana (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
Biodiversity has many variations in shape, appearance, number and characteristics that are seen in improving ecosystems, species levels and genetic levels. The homegarden can create environmental conservation, especially local trees. Tambakrejo Village is an example of an urban area located in Jombang District with the highest population density of 6.88 people/km2 with a population of 12,279 people. This study aimed to determined the types of trees in the homegarden area of Tambakrejo Village, Jombang Regency. Data collection was carried out by observing each type of tree in 68 observation sample plots in the Tambakrejo Village homegarden area. The results of the observations found 414 tree species that belong into 26 types of families. Most of these tree species came from the Anacanrdiaceae family as many as 91 tree species.